Scale of Organizational Structure Components (SOCS): Evidence of Validation of a Theoretical Model - Leandro Trigueiro-Fernandes; Joyce Mariella Medeiros Cavalcanti; Marcelo Victor Alves Bila; Miguel Eduardo Moreno Añez (BBR: Brazilian Business Review)
This study aims to proposed and validate a scale of organizational structure components (SOSC) from the latent components identified in the exploratory study by Trigueiro-Fernandes (2014), inspired by the design parameters of Mintzberg (2012). The survey was conducted in 26 public and private organizational units. Confirmatory Factor Analysis was employed to assess the SOSC model properties and whether they fit the theory. The results show that the scale has acceptable goodness of fit, verifiable through adjustment indexes such as χ²/df, RMSEA, CFI, TLI, and SRMR, as well as composite reliability, convergent and discriminant validity tests. The identified organizational structure components were formalization, communication, decentralization, training and internalization, departmentalization, and hierarchy. The results allow us to infer that the structure is the means by which the interactions between people and processes are organized and as coordination mechanisms for achieving the organizational mission are identified.